The complete chloroplast genome of Stachyurus himalaicus - Yushuang Chen; Rui Li; Shubao Wang; Shuang Xiong; Yuan Huang (Mitochondrial DNA. Part B. Resources)
The complete chloroplast genome of Stachyurus himalaicus Hook. f. et Thoms. ex Benth. was sequenced and analyzed. The circular cp genome of S. himalaicus is 162,642 bp in length, consisting of inverted repeats (IRs; 26,437 bp), small single-copy (SSC; 18,762 bp), and large single-copy regions (LSC; 91,006 bp). The genome contains 131 genes (86 protein-coding, 37 tRNA, 8 rRNA) with 37.0% GC content. Phylogenetic analysis revealed the monophyly of Stachyuraceae, and S. himalaicus was sister to the other 3 Stachyurus species examined. Our results provide useful genetic resources for further studies on the evolution and phylogeny of Stachyuraceae.